Association Between Cardiovascular Risk Factors and Carpal Tunnel Syndrome in Pooled Occupational Cohorts. Issue 1 (January 2016) - Hegmann, Kurt T.; Thiese, Matthew Steven; Kapellusch, Jay; Merryweather, Andrew S.; Bao, Stephen; Silverstein, Barbara; Wood, Eric M.; Kendall, Richard; Wertsch, Jacqueline; Foster, James; Garg, Arun; Drury, David L.
Abstract : Objective: The aim of the study was to ascertain if cardiovascular (CVD) risk factors are carpal tunnel syndrome (CTS) risk factors. Methods: Analysis of pooled baseline data from two large prospective cohort studies (n = 1824) assessed the relationships between a modified Framingham Heart Study CVD risk score both CTS and abnormal nerve conduction study prevalence. Quantified job exposures, personal and psychosocial confounders were statistically controlled. Odds ratio and 95% confidence intervals were calculated for individual risk scores. Results: There was a strong relationship between CVD risk score and both CTS and abnormal nerve conduction study after adjustment for confounders, with odds ratios as high as 4.16 and 7.35, respectively. Dose responses were also observed. Conclusions: In this workplace population, there is a strong association between CVD risk scores and both CTS and abnormal nerve conduction study that persisted after controlling for confounders. These data suggest a potentially modifiable disease mechanism.